INFLUÊNCIA DOS TRAÇOS CULTURAIS NACIONAIS NA FORMAÇÃO DE APL´S – O CASO DAS EMPRESAS DE ESQUADRIAS DO APL DA MADEIRA - Rodrigues, Fernanda; Ihlenfeld, Renate; Oliveira, Rafael de Souza; Daltoé, Claudir José; Silva, João Carlos Garzel Leodoro da (Floresta, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]--> O setor florestal tem, historicamente, no Sul do Brasil, importância estratégica. O presente estudo buscou identificar o grau de presença das chamadas características culturais nacionais na região do Arranjo Produtivo Local (APL) da madeira de União da Vitória – Porto União. Dentre as características analisadas – personalismo, protecionismo, aversão à incerteza, formalismo, “jeitinho”, receptividade ao estrangeiro e orientação ao curto prazo –, apenas duas representaram diferentes níveis de presença entre as empresas participantes e não participantes do APL: formalismo e receptividade ao estrangeiro. As características mais marcantes foram a orientação ao curto prazo e o protecionismo. Com base nessa realidade, para potencializar o processo de formação e implementação do APL, recomenda-se: i) profissionalização do setor; ii) realização de estudos de mercado e de competitividade do segmento; iii) implementação de sistemas de qualidade; iv) adoção de soluções com base na realidade local; v) trabalhar a importância da gerência local e a participação de todos os interessados; e, por fim, vi) elaboração de um planejamento regional com horizonte temporal, com respectivo acompanhamento da execução. Palavras-chave: Características culturais nacionais; APL; planejamento. Abstract Influence of the Brazilian national cultural traits in the formation of the APL´S – The case of the enterprises of the wood’s local productive arrangement. Historically, the Forest sector in South Brazilian is strategic importance. This study aimed to identify the level of presence of the main Brazilian national cultural traits in the Wood’s Local Productive Arrangement (APL) of União da Vitória – Porto União, southern Brazil. Among the analyzed characteristics: personal relations, protectionist, formalism, local and informal procedures of finding ways to solve problems, aversion to uncertainty, receptivity and short-term orientation only of them, two showed difference level of presence among participants of APL and non-participants enterprises – formalism and receptivity. The most outs tan ding national cultural traits found were short-term orientation and protectionism. To help the formation and implementation of the APL, taking into account the scenarios identified, some actions are suggested: I) sector’s professionalization, II) development of market and sector’s competition studies, III) implementation of quality systems, IV) solutions based in the local reality, V) development of local management and stakeholders participation, and, VI) preparation of a long-term regional planning, with implementation of monitoring and evaluation system. Keywords: Brazilian national cultural traits; APL; planning. <!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] -->